An empirical study on the performance of fundamental indices vs. traditional market capitalization-weighted indices as applied to the Philippine stock market: A smart beta strategy application - Calaquian, Maria Carmela (Animo Repository, 2017)
Recent years have seen the rise of smart beta strategies especially fundamental indices among investors and portfolio managers. Fundamental indexation, which was introduced by Arnott, Hsu and Moore (2005), is an alternative to the conventional market capitalization-weighted index as it makes use of price-indifferent accounting/fundamental measures in determining the weights to be assigned to a specific stock in an index. Recent studies claim the outperformance of these fundamental indices as against their market capitalization-weighted counterparts. According to Treynor (2005), the suboptimal performance of market capitalization-weighted indices is due to its tendency to overweight overvalued shares and underweight undervalued shares (Treynor, 2005) given that the weights assigned are based on share prices (market capitalization), which may be too noisy relative to their fundamentals. This study finds that fundamental indices delivers superior performance compared to the traditional market capitalization-weighted index as applied to Philippine listed stocks for the period 2005 to 2015. The study does not aim to re-compute the PSEi price, but rather it introduces a new way of selecting index constituents based on fundamental factors. Fundamental indices were constructed based on book value, operating cash flow, revenues and dividends. In addition, through regression analysis, the study finds that the major determinant that led to the outperformance of the fundamental indices in the Philippines is its value bias, i.e. fundamental indices put more weight on undervalued stocks.